Geochemical Characteristics and Evaluation Criteria of Overmature Source Rock of the Laiyang Formation in Well LK-1, Riqingwei Basin, Eastern China - Yang Chen; Yaoqi Zhou; Tengfei Zhou; Hanjie Zhao; Hongyu Mu; Chun Zhang (Energies, 2023)
Total organic carbon (TOC) and hydrocarbon generation potential (Pg) are essential parameters for the qualitative evaluation of source rock and the basis for evaluating hydrocarbon resources in petroliferous basins. However, there will be some deviations in evaluating hydrocarbon resources of overmature source rock by using TOC and Pg. The super-thick overmature source rock of the Early Cretaceous Laiyang Formation was found in well LK-1, the Riqingwei Basin. To accurately understand the oil and gas potential of the Riqingwei Basin, this paper conducted a systematic organic geochemical analysis of the overmature source rock of the Early Cretaceous Laiyang Formation found in well LK-1. Combined with the results of previous thermal simulation tests on hydrocarbon generation of low-maturity samples in the Jiaolai Basin, the original total organic carbon (TOC0) content of source rock in well LK-1 was recovered and the evaluation criteria of overmature source rock was established. Results: (1) The average TOC content of well LK-1 source-rock samples is 1.25 wt.%, and the average Pg content is 0.11 mg/g. The type of organic matter is mainly type II2, including a small amount of type II1 and type III. The average reflectance of vitrinite (Ro) is 4.35%, which belongs to overmature source rock of a poor–fair level and mixed kerogen. (2) After recovery calculation, these samples’ original hydrocarbon generation potential (Pg0) contents ranged from 0.63 to 108.1 mg/g, with an average value of 6.76 mg/g. Furthermore, the TOC0 contents of the analyzed source-rock samples ranged from 0.62 to 30.6 wt.%, with an average value of 2.01 wt.%. It belongs to fair–good source rock, showing better hydrocarbon generation potential. (3) According to the relationship between the Pg0, Pg and TOC content, the evaluation standard for overmature source rock in well LK-1 was established. Under the evaluation standard of overmature source rock, a source rock with a TOC content exceeding 0.6% and a Pg content greater than 0.1 mg/g can be identified as a good source rock. This paper provides a foundation for the fine classification and evaluation of the overmature source rock of the Riqingwei Basin.